Red de espacios verdes públicos, aplicado a la propuesta de un corredor verde urbano en la cabecera cantonal de Otavalo - Chicaiza De la Cruz, Erikc Michael (2023)
The purpose of the degree work is to contribute to the development of urban planning in the cantonal capital of Otavalo through plans and strategies for public green spaces and to enhance the green surface per inhabitant due to the high deficit that exists in the city. This work is based on the study of identification, classification and evaluation of the public green spaces of the cantonal capital, the se spaces are parks, civic parks, linear parks, playgrounds, boulevards, sports fields, water margins where one of the characteristics Fundamental is that 50% or more of its surface is permeable. Once the public green spaces have been identified and classified, the evaluation is carried out using three methodologies: quantita tive, qualitative and mixed\; The quality evaluation of public green spaces allows us to appreciate the state of the spaces, their level of functioning and identify the problems of these spaces. The life surveys of users allow us to visualize the level of use and social cohesion in the spaces. and the green surface per inhabitant determines the lack of permeable spaces in the city of a public nature. With the analysis of the problem, it is proposed to generate a network of public green spaces for the cantonal capital of Otavalo, this network is made up of the existing public green spaces in the city, the proposal of two urban forests on the Cotama and Pucara hills, that are connected by three ecological water corridors as the main articulating elements, which are the Tejar, Jatunyacu and Machangara rivers\; To complement this network, it is developed through urban green corridors on the avenue and streets that are complemented by ecological trails. Finally, a multifunctional green corridor is proposed on the current E35 as a connecting element between public green spaces and ecological corridors. This urban green corridor has the purpose of generating green spaces that improve the quality of life of Otavaleños through recreation and leisure spaces that allow social cohesion of users. This project benefits the Otavalo population by generating a high rate of green surface per inhabitant, promoting the care and pro jection of quality public green spaces as mitigating elements against climate change and its high benefits for human life